2013
DOI: 10.3109/15368378.2013.795156
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low-frequency magnetic fields can impair spermatogenesis recovery after reversible testicular damage induced by heat

Abstract: Male infertility is often related to reproductive age couples experiencing fertility-related issues. Men may have fertility problems associated with reversible testicular damage. Considering that men have been increasingly exposed to extremely low-frequency magnetic fields generated by the production, distribution and use of electricity, this study analyzed whether 60 Hz and 1 mT magnetic field exposure may impair spermatogenesis recovery after reversible testicular damage induced by heat shock using rats as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Effect of a 60 Hz MF exposure on number (A), motility (B), and abnormality (C) of sperm from epididymis in rats. A recent report showed that ELF MF can impair spermatogenesis recovery after reversible testicular damage induced by heat shock (43 8C for 12 min) in rats [Tenorio et al, 2014]. Significant difference was decrease in the number of sperm in 200 mT.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Effect of a 60 Hz MF exposure on number (A), motility (B), and abnormality (C) of sperm from epididymis in rats. A recent report showed that ELF MF can impair spermatogenesis recovery after reversible testicular damage induced by heat shock (43 8C for 12 min) in rats [Tenorio et al, 2014]. Significant difference was decrease in the number of sperm in 200 mT.…”
Section: Discussionmentioning
confidence: 94%
“…Further, Li et al [2010] showed that exposure to power frequency MFs in humans produced a higher risk of poor sperm quality, as well as decreased sperm density, vitality, normal morphology, and motility. A recent report showed that ELF MF can impair spermatogenesis recovery after reversible testicular damage induced by heat shock (43 8C for 12 min) in rats [Tenorio et al, 2014]. Thus, it can be speculated that increased testicular germ cell apoptosis may be an important feature of testicular function in MF exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Testosterone level in mice exposed to EMF for 16 weeks was not modified despite the marked increased germ cell apoptosis [26]. Differentiating spermatogenic cell apoptosis may occur in the early phase of ELF-MF exposure without alteration in the peripheral testosterone level [25,27,52], supporting the idea that the biological effect of MF exposure on germ cell apoptosis may not be hormonally mediated. Summarizing, cellular proliferation of Leydig cells may be induced at a relatively early phase after ELF-MF exposure.…”
Section: Hypothalamic-pituitary-gonadal Axis and Emf Exposurementioning
confidence: 91%
“…In rats, ELF-MF can impair spermatogenesis recovery after heat-induced reversible testicular damage [52]. Ultrastructural changes in spermatogonia and spermatocyte occurred earlier than degeneration of Sertoli cells, suggesting that spermatogenic cells may be more sensitive to EMF exposure than Sertoli cells.…”
Section: Effect On Sperm Count and Testis Weightmentioning
confidence: 92%
“…After producing the testicular histological sections, 50 images (.sfc format, 2048x1536 pixels) per animal were captured using an optical microscope (Motic BA300, Hong Kong, China), coupled to a digital camera MOTICAM 2300 (Motic, Hong Kong, China), connected to a microcomputer [Tenorio et al 2014]. Leydig cell area measurement was performed using the biometric software Images Plus 2.0 (Motic) calibrated for each objective.…”
Section: Computational Histometrymentioning
confidence: 99%